MODEL PROCESS AND CRITERIA FOR SELECTION OF COMPONENTS COMPUTER ORIENTED TRAINING ENVIRONMENT POSTGRADUATE TEACHER EDUCATION - Kolos, К.Р. (Journal of Information Technologies in Education (ITE), 2014)
The study identified current priorities of postgraduate pedagogical education, the implementation of which is seen in the skillful integration of modern information and communication technologies in teaching and learning process training courses teaching staff, which in turn requires a clear conceptual framework on criteria for the selection of the components of computer-based learning environment establishment of Postgraduate Teacher Education was developed and proved the model selection process components of computer-based learning environment establishment of Postgraduate Teacher Education, which is based on: the goals and objectives of postgraduate education, didactic requirements for computer-based learning environment institution of postgraduate education, fund existing / prospective component selection criteria of computer-based learning environment establishment of Postgraduate Teacher Education components, grouping potential component quantization method, selection and analysis of signatures potential components, identified the need and role of experts in information and communication technologies in education in the selection of components for computer-based learning environment establishment of Postgraduate Teacher Education solving instructional requirements for computer-based learning environment post-graduate teacher training in education,a concept of "selection criteria components of computer-based learning environment post-graduate teacher education", the criteria for selection of components of computer-based learning environment establishment of Postgraduate Teacher Education: innovation perspective, information technology, value-semantic, ergonomic, professionally meaningful, relevant, standardization,reliability, compatibility, Mobility and Coordination, learner-oriented, cost, integration and education - and their performance.